TEACHING CULTURAL IDENTITY VIA FASHION KEBAYA AS EDUCATIONAL FRAMEWORK IN MALAY CINEMA (1950–2000) - Halim, Hazirah; Aris, Asliza; Zainuddin, Nasaie (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
The kebaya, a traditional Malay garment, transcends fashion by encapsulating ethnic identity, social conduct, and evolving notions of femininity. This paper examines the portrayal of the kebaya in classic Malay cinema from 1950–2000 and recontextualises it as an educational tool for teaching cultural identity, history, and social behaviour. Using a qualitative object oriented methodology, films such as Hang Tuah (1956), Ibu Mertuaku (1962), and Masam Masam Manis (1965) were analysed for costume design, symbolism, and narrative function. The findings underscore three principal pedagogical themes: modesty and ethics, socioeconomic class, and femininity shaped by modernisation. These themes illustrate how the kebaya functioned as a cultural emblem representing morality, social stratification, and shifting gender dynamics in postcolonial Malaysia. The study highlights the kebaya as an effective instrument for object based learning, critical analysis, and interdisciplinary instruction across fashion studies, cultural studies, and media education. Despite challenges related to archival accessibility and cultural sensitivity, there are promising opportunities for enhanced teaching through digital archives, cross cultural comparisons, and innovative curriculum development. Overall, the study strengthens cultural pedagogy by framing the kebaya as both a historical garment and an educational lens that bridges tradition, modernity, and learning.